Helical itinerant MnSi magnet: magnetic phase transition. (December 2017) - Stishov, S M; Petrova, A E
Abstract: New studies of the phase transition and phase diagram of the chiral MnSi magnet are reported. New results are obtained in the course of analysis of experimental data on heat capacity, thermal expansion, elastic properties, electrical resistance, neutron scattering, and theoretical modeling.